Effects of 7,12-Dimethylbenz(a)anthracene on Apoptosis of Breast Cancer Cells through Regulating Expressions of FasL and Bcl-2 - Lin, Renzhi; Guan, Zihan; Zhou, Qi; Zhong, Jijun; Zheng, Chenhui; Zhang, Zhuoni (Cellular and Molecular Biology, 2022)
To provides a reference basis for the apoptosis of breast cancer (BC) cells and the carcinogenesis of BC, the effects of 7, 12-dimethylbenz (a) anthracene (DMBA) on apoptosis regulators FasL and B-cell lymphoma-2 (Bcl-2) were investigated. In this study, 62 female C57BL/6 mice aged from 4 to 6 weeks were randomly divided into control group (CG) and test group (TG), with 31 mice in each group. The TG was given DMBA solution by gavage at a dose of 50 mg/kg, and the CG was given normal saline of equal volume. On the second day after the experiment, all the mice were killed by cervical dislocation. The morphology of the mammary gland was observed by hematoxylin-eosin (HE) staining, and the differences of FasL and Bcl-2 protein expression (PE) were detected by immunohistochemistry. The mRNA expression levels of FasL and Bcl-2 were detected by quantitative real-time PCR (qPCR). Breast cell apoptosis status of mice in the two groups was detected by the terminal deoxyribonucleotidyl transferase (TdT)-mediated biotin-16-dUTP nick-end labelling (TUNEL) method. The results showed that after HE staining, the tumor cells in the TG were stacked up to form a substantial structure. The expression level of FasL protein in the CG was greatly lower than that in the TG, and the positive rate (PR) was 20.25%, which was greatly lower than that of 89.65% in the TG (P<0.01). The expression level of Bcl-2 protein in the mammary gland tissues (MGTs) of mice in the TG was greatly higher than that of the CG, and its PR was 87.96%, which was greatly higher than that of 31.48% in the CG (P<0.01). The expression levels of FasL mRNA in the MGTs of mice in the TG and CG were 5.82±4.37 and 1.27±0.12, respectively, and there was a statistically obvious difference (P<0.05). The mRNA expression levels of Bcl-2 in the TG and the CG were 18.97±2.65 and 2.02±0.54, respectively, and there was an extremely obvious difference (P<0.01). The apoptosis rate of mammary gland cells in the TG was (19.79±3.53) %, and that in the CG was (2.93±0.28) %, and there was an extremely obvious difference (P<0.01). It indicated that DMBA inhibited the apoptosis of BC cells by regulating the up-regulation of FasL and Bcl-2 expression.